Dry-hopping: the effects of temperature and hop variety on the bittering profiles and properties of resultant beers - Oladokun, O.; James, S.; Cowley, T.; Smart, K.; Hort, J.; Cook, D. (Fachverlag Hans Carl GmbH, 2017)
This paper reports the effects of dry-hopping at 4 and 19 °C for a low alpha versus high alpha hop variety on the resulting profiles of non-volatile hop acids (humulinones, iso-a-acids, a-acids). In a dry-hopping study conducted over 2 weeks, we found a significant increase in humulinone concentration driven principally by hop alpha acid content and the duration of dry-hopping. Conclusive evidence of iso-a-acid losses during dry-hopping (by adsorption onto spent hops) is presented, in addition to a significant increase in a-acid concentrations, which was observed only for beers dry-hopped at 19 °C with the high alpha hop variety. Measured beer parameters (especially at 19 °C) revealed an increase in pH, ABV (%), and a decrease in beer density during dry-hopping - from which we conclude that further attenuation of beer occurred during dry-hopping. The polyphenol content of beers was found to increase substantially with dry-hopping time, whilst both temperature and hop variety were found to be significant factors determining the amounts of polyphenols extracted. Finally, analysis of the spent hop slurry (recovered after 14 days of dry-hopping) confirmed that the residual content of hop acids (a-acids, their oxidised derivatives and polyphenol content), makes these materials - currently treated as waste - of potential value for re-use in the brewing process.